VOLATILITY DYNAMICS OF ISLAMIC AND CONVENTIONAL STOCKS IN INDONESIA: EVIDENCE FROM GARCH MODELS - Abdul Gafur Rinaldi; Yasmin (SHACRAL: Shari'ah Economics Review Journal, 2025)
Understanding stock market volatility is essential for effective risk management and portfolio decision-making, particularly in emerging markets characterized by high uncertainty. Indonesia’s capital market provides a unique setting for volatility analysis due to its dual structure, which accommodates both Islamic (Shariah-compliant) and conventional stock indices. This study examines and compares the volatility dynamics of the Jakarta Islamic Index (JII) and the Indonesia Composite Index (IHSG) using a Generalized Autoregressive Conditional Heteroskedasticity (GARCH) framework. Employing daily closing price data from the Indonesia Stock Exchange for the period 2020–2025, this research applies the GARCH(1,1) model to capture volatility clustering, persistence, and time-varying risk characteristics in both market segments. The empirical results reveal notable differences in volatility behavior between Islamic and conventional stocks. Descriptive statistics indicate that JII exhibits higher unconditional volatility than IHSG, as reflected by a larger standard deviation and wider return range. Stationarity tests confirm that both return series are suitable for GARCH modeling. The GARCH estimation results show that IHSG has a higher ARCH coefficient, suggesting a stronger short-term reaction to market shocks, while JII displays a higher GARCH coefficient, indicating greater long-term volatility persistence. The volatility persistence parameter (α + β) is close to unity for both indices, implying that volatility shocks dissipate slowly in both Islamic and conventional stock markets. These findings contribute to the growing literature on Islamic finance by providing updated evidence on volatility dynamics in Indonesia’s capital market. The results have important implications for investors, portfolio managers, and policymakers, particularly in terms of risk assessment, portfolio diversification, and the development of Islamic capital market infrastructure. Overall, the study highlights that while Islamic and conventional stocks share common volatility features, their transmission mechanisms and persistence patterns differ, underscoring the importance of time-varying risk models in investment analysis.